O sonetach polskich romantyków - Staszewska, Dorota (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
This article treats of sonnets in works of Polish romantics, conciders the popularity of sonnet in Romantiscism and tries to define the consciousness of poets’ genre form first half of XIX century. It also includes the catalogue of Polish romantic sonnets. Remarkable may seem, that the genre of such rigorous structure turn to be the most popular form of expression in the epoch which broke very scheme. Undoubtedly, this is due to Adam Mickiewicz who published two series of sonnets in 1826 in Moscow, under the title Sonety. Mickiewicz introduced sonnetmania among many less known poets of this epoch. What was so impressive for artists such as Mickiewicz and Słowacki to follow this pattern of writing? Romantic poets could have been impressed by the possibility of polemic with traditional erotic themes, as well structure of the genre, wihich includes plenty of limitations, which seemingly restricted the artist, actually enables wide interpretations. The popularity of a sonnet as a genre could have resulted form the programmatic opposition to the classics. Besides the sonnets arranged in series were best suited for expressing the experience of an individual facing the world differently. Sonnets inscribed remarkable in ormantic fragment of poetics.